الآخر في الرواية الجزائرية ما بعد الكولونيالية - طويل, سعاد (جامعة الوادي - University of Eloued, 2020)
ملخص: تقوم هذه الدراسة على بحث حضور الآخر، والتأثيرات التي خلفها المستعمِر على المستعمَر بعد الاستقلال، بغية الوقوف على أشكال هذا التأثير وتجلياته؛ التي تظهر في الدين والثقافة واللغة والفكر، وتمثل الرواية بوصفها نصا أدبيا أكثر النصوص التي تتجلى فيها هذه الأشكال، وتبرز تلك العلاقة بين الطرفين وتداعياتها، وذلك ما نسعى لبحث تجلياته في الرواية الجزائرية ما بعد الكولونيالية. Abstract: this study examinesthe presence of the other and the effects that the colonizer left over the colonized after independence, in order to identify the forms and manifestations of this influence, which appear in religion, culture, language and thought ..., and perhaps the novel and as a literary text was the most one that these forms are evident and highlighting that relationship between The two parties and their repercussions, and this is what we seek to discuss in the Algerian novel.
مقال
Keywords: key words : postcolonialism, postcolonial novel, Algerian novel, the other , ego